Control and Media Sessions: lAX with RSW Control Criteria - Manjur, S. Kolhar; Anas, F. Bayan; Tat, Chee Wan; Sureswaran, R.; Omar, Aboubdalla (2008)
This paper discusses technical issues related to delivery and control of IP multimedia services, such as multimedia conferencing, involving heterogeneous end terminals. In particular, it proposes the design of an experimental system for interworking between InterAsterisk eXchange Protocol and RSW session and call control signaling protocols.